A Two Step Synthesis Route of WC Nanopowders - Guan, Ruqi; Hu, Kailing; Wang, Lihua; Chen, Youjian (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
Here, a novel molten salt route to synthesize ceramic WC nanopowders was presented. Compared to the traditional synthesis procedures, this method is relatively low cost involving two-step synthesis route. In the argon atmosphere at 650 oC, the powders were the mixed WC and W2C phases. These synthesized powders were transferred to a small crucible (30 mL) containing molten salt, which were put into a 500 mL crucible with some carbon powder in it as reducing atmosphere, followed by maintaining the reaction temperature at 1100 Â°C for 1 h. The phase purity and composition were characterized by the powder X-ray diffractometer (XRD). It was found that W2C was transformed thoroughly into WC, which indicated the successful synthesis of WC powders using this method. The mechanism of the reaction process in molten salt has been discussed finally. The thermogravimetric analysis indicated that the as-prepared samples showed good thermal stability and oxidation resistance in high temperature. The methodology reported in this work was fundamentally important, which may find potential industrial applications.